Optimizing antifungal therapy: a systematic review of pharmacist interventions, stewardship approaches, and outcomes - Akbar, Zunaira; Aamir, Muhammad; Saleem, Zikria (Frontiers in Medicine, 2024)
Specific evidence regarding pharmacist role in antifungal stewardship is emerging. The purpose of this review is to identify Pharmacist driven antifungal stewardship interventions to optimize antifungal therapy. A systematic review was conducted using PRISMA guidelines. Data (2018Data ( -2023) ) were collected through Google scholar and PubMed. Owing to variations in interventions and outcome metrics, the collected data were presented descriptively. Conclusions were derived through a qualitative synthesis of the identified findings. A total of 232 articles were retrieved and after applying inclusion and exclusion criteria 27 were included in review. Among 8 studies evaluating impact of Pharmacist interventions on antifungal consumption, 6 studies reported significant decline in DDD/1000 patient days and DOT/1000 patient days, one reported non-significant decline and one reported increase in utilization of echinocandins. Educational intervention was the most commonly used stewardship approach. 19 studies reporting data on various clinical outcomes. Mortality and length of hospital stay remains non-significant, but occurrence of ADR decreased significantly, and quality of antifungal use improved significantly. Pharmacist led AFS has the potential to enhance the effectiveness of antifungal treatments by improving their overall quality, reduction in consumption and adverse events. Health care system should encourage multidisciplinary collaboration where pharmacists play a central role in decision-making processes regarding antifungal use.